DYNAMIC NEUROMUSCULAR STABILIZATION LEBIH MENINGKATKAN KESEIMBANGAN DINAMIS DARIPADA PERCEPTUAL MOTOR PROGRAM PADA ANAK DOWN SYNDROME USIA 7-15 TAHUN DI YAYASAN PRADNYAGAMA DENPASAR - Ulfa, Merinda; Tirtayasa, Ketut; -, Wahyuddin; Purnawati, Susy; Sundari, Luh Putu Ratna; Irfan, Muhammad (Sport and Fitness Journal; Volume 7, No.2, Mei 2019DO - 10.24843/spj.2019.v07.i02.p05, 2019)
Background: Disorder of dynamic balance is often found in children with Down syndrome which causes difficulty in maintaining posture against impending disorders. If this is left it will certainly cause problems of further motor development. Purpose: To prove the physiotherapy intervention that can improve dynamic balance among children with down syndrome 7-15 years. Methods: The research is true experimental with pre-test and post-test group design. This study used 24 subjects in 2 groups, group 1 (n=11) given dynamic neuromuscular stabilization on while group 2 (n=11) given perceptual motor program. Divided randomly into 2 groups that is group 1 dynamic neuromuscular stabilization and group 2 perceptual motor program. The exercise is held 3 times a week in 6 weeks. Measurements of this dynamic balance are using sixteen balance tests. Result: The paired sample t-test statistical test in group 1 showed a significant difference with value (p <0.001) on mean before intervention 48.5±5.428 and after intervention 72.75±4.413. The paired sample t-test statistical test in group 2 showed a significant difference with value (p <0.001) on mean before intervention 48.5±5.3 and after intervention 69.42±4.379. Different test between group 1 and 2 using independent sample t-test showed a significant difference with value (p<0.001). Conclusion: The conclusions are dynamic neuromuscular stabilization is better than perceptual motor program in improving dynamic balance among children with down syndrome 7-15 years at Pradnyagama Foundation Denpasar.